2020
DOI: 10.1097/jom.0000000000001968
|View full text |Cite
|
Sign up to set email alerts
|

Injury, Illness, and Mental Health Risks in United States Domestic Mariners

Abstract: Objective: Describe health conditions and injury and illness rates in a population of United States mariners, an understudied workforce vital to economic security. Methods: In this survey study, mariner health data was collected and analyzed to provide injury and illness rates (including mental health conditions) and associated risk factors. Results: In this mariner population of highly tenured vessel master… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“… 7 Lefkowitz et al (2019) [ 34 ] North America (United States of America) Secondary descriptive study Data from large international marine insurance from 2007–2015 278 international seafarers N/A Mental illness including social withdrawal, mood swings or other concerning change was found 3.9 per 100,000 person-years. 6 Lefkowitz et al (2020) [ 35 ] North America (United States of America) Cross-sectional study Self-administered questionnaire at piloting training center 233 domestic seafarers PHQ-9 Depressive symptom was 16%. Obesity (BMI > 35 kg/m 2 ), poor sleep quality, and anxiety were associated with depressive symptom.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 7 Lefkowitz et al (2019) [ 34 ] North America (United States of America) Secondary descriptive study Data from large international marine insurance from 2007–2015 278 international seafarers N/A Mental illness including social withdrawal, mood swings or other concerning change was found 3.9 per 100,000 person-years. 6 Lefkowitz et al (2020) [ 35 ] North America (United States of America) Cross-sectional study Self-administered questionnaire at piloting training center 233 domestic seafarers PHQ-9 Depressive symptom was 16%. Obesity (BMI > 35 kg/m 2 ), poor sleep quality, and anxiety were associated with depressive symptom.…”
Section: Resultsmentioning
confidence: 99%
“…The general characteristics of 24 studies are demonstrated in Table 2 . Sixteen studies were conducted in Europe [ 14 29 ], five in Asia [ 6 , 30 – 33 ] two in North America [ 34 , 35 ] and one in South America [ 36 ]. Twenty-two studies were quantitative [ 6 , 14 24 , 26 28 , 30 – 36 ] and two were qualitative [ 25 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations